Mechanical dissipation from charge and spin transitions in oxygen-deficient SrTiO3 surfaces - Marcin Kisiel (Nature Portfolio, 2018)
Non-contact atomic force microscope (AFM) dissipation contains rich information on the electron, phonon and spin states, but has been poorly understood. Here the authors demonstrated that tip-induced charge and spin state transitions in oxygen vacancies at SrTiO3 surface are revealed by AFM dissipation measurements.